Maximizing The Potentials of Nature Tourism through Contextual English Training at Towil Fiets Desa Bandar (Sentolo) - Dangin, Dangin; Hartati, Elysha (Journal Of Human And Education (JAHE), 2024)
This program is in line with its main goal to make nearby region a suitable tourism destination that values ​​linguistic diversity and prioritizes the needs of visitors. This program was based on initial findings that Towil Fiets as a potential international tourism destination still got obstacles in English as the main language of communication. It was found that administrative staff and tour guides still had a moderate level of English proficiency especially for tourism. They also demonstrated limited contextual linguistics aspects. This program was implemented for about two months as an effort to solve the problems. The first point was focused on comprehensive language training programs addressed to the specific needs of each group. The second pointer was in-depth language workshops complemented by practical on-site training sessions at key tourist attractions. The results showed that the participant could get deeper conversation and wider explanation related to the context of tourism object.